A menipeia da idade contemporânea: a COVID-19 (e o mundo) segundo South Park. - Carvalho, Júlio César Brandão (2024)
This study, conducted as part of the Doctorate in Language Sciences, proposes an in-depth analysis of the animated series “South Park”, exploring its carnivalesque nature and the elements of Menippean satire that permeate it. Our research delves into how the series addresses cultural and social issues through a lens that incorporates ambiguities, ambivalences, and the grotesque humor typical of carnival contexts and Menippean traditions. The series' unique ability to expose contradictions and absurdities in US (and sometimes global) pop(ular) culture and politics has been fundamental to its continued resilience and relevance over the decades. This characteristic aligns with Mikhail Bakhtin's concept of “carnivalization”, where carnival celebrations are marked by apparent chaos and the temporary inversion of hierarchical relationships between individuals.By examining the everyday lives of the main characters – Stan, Kyle, Kenny, and Cartman – we seek to understand how the show portrays seemingly improbable but often revealing events that offer insightful commentary on contemporary society. Essentially, our overarching objective is to analyze the presence of the fundamental characteristics of Menippean satires, as outlined by Bakhtin, in the animation South Park, seeking to highlight the versatility and longevity of this ancestral genre, which influenced the creation of numerous other artistic forms. Initially, we aimed to identify how the carnivalesque worldview manifests in the specials focusing on the COVID-19 pandemic, released in 2020 and 2021, by examining how the series employs carnival elements to construct its narratives. Furthermore, we investigated how the cartoon relates to the journalistic characteristic typical of Menippean literature, configuring itself as a carnivalized representation of contemporary times capable of reflecting on and commenting on social events. Therefore, this study allowed for an appreciation of South Park not only as a cheeky and irreverent animated series but also as a sagacious descendant of a literary and philosophical tradition, which, like one of its protagonists, the boy Kenny, seems to be immortal. This intrinsic connection underscores not only the flexibility and longevity of Menippean satire but also the continuity of humor and satire as critical tools. In various contexts, the art of challenging conventions persists as a guiding thread in creative expression, reflecting the evolutionary nature of society and the perpetuity of human questioning.